Epigenetics and diet: how does food regulate our genes? - Acevedo-Espinola, R. (2024)
In recent decades, research into how our cells function using cellular and molecular approaches has further opened our understanding of how homeostasis is disrupted by environmental insults. Unhealthy diet over time generates a wide range of problems that lead to morbidity and mortality. Previously, the causes of diseases were attributed solely to the genetic makeup of individuals, however, epigenetics emerged to help understand how lifestyles can influence the expression of an individual's genes. Therefore, in this review article, we discuss recent evidence indicating that dietary components can modulate gene function through epigenetic control (e.g., DNA methylation, histone modifications, and microRNAs) to maintain homeostasis. In addition, it is discussed what happens when harmful nutritional habits predominant (e.g., high fat and sugar diet and low consumption of vitamins-rich foods); a situation that deteriorates and interrupts the way our genes work. The importance of this field lies in the fact that nutritionists, in the future, could direct personalized nutritional therapies and, above all, they could practice health promotion with an integrated knowledge on how diet regulates our genes.